2020
DOI: 10.1186/s12985-020-01432-9
|View full text |Cite
|
Sign up to set email alerts
|

The chest CT features of coronavirus disease 2019 (COVID-19) in China: a meta-analysis of 19 retrospective studies

Abstract: Objective Aimed to summarize the characteristics of chest CT imaging in Chinese hospitalized patients with Coronavirus Disease 2019 (COVID-19) to provide reliable evidence for further guiding clinical routine. Methods PubMed, Embase and Web of Science databases were searched to identify relevant articles involving the features of chest CT imaging in Chinese patients with COVID-19. All data were analyzed utilizing R i386 4.0.0 softwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“… 27 , 28 However, other special classic signs, including reverse halo sign, intralesional traction bronchiectasis and lymphadenopathy were rare. Similarly to our results, Yang et al, 29 reported the low frequency of the intrathoracic lymph node enlargement, pleural effusions, the lesion distribution in lung of central, unifocal, and unilateral.…”
Section: Discussionsupporting
confidence: 92%
“… 27 , 28 However, other special classic signs, including reverse halo sign, intralesional traction bronchiectasis and lymphadenopathy were rare. Similarly to our results, Yang et al, 29 reported the low frequency of the intrathoracic lymph node enlargement, pleural effusions, the lesion distribution in lung of central, unifocal, and unilateral.…”
Section: Discussionsupporting
confidence: 92%
“…, Bao C. et al[57], Zheng Y. et al[58], Zhu J. et al[59], Zhou X. et al[70], Homsi M. et al[71], and Yang H. et al[72] reported GGO to be 77 18. %, 83.31 %, 78 %, 68.1 %, 68 %, 71.70 %,and 79 % respectively.…”
mentioning
confidence: 99%
“…Typical COVID-19 radiological features are CT patterns of acute viral pneumonia including bilateral peripheral ground-glass opacities, crazy paving, air space consolidation, vascular enlargement, and reticulations. Importantly, mediastinal lymphadenopathies that were found in all cases, and pleural effusions or thickening reported in 4/6 cases, are extremely rare in COVID-19 patients with 0.03 combined proportions reported by meta-analysis ( Long et al, 2020 ; Yang et al, 2020 ). Radiological features of the two moderate cases 5 and 6 associated inflamed lymph nodes in mediastinum with chestnut shaped nodules in both lungs without any patterns of COVID-19.…”
Section: Mainmentioning
confidence: 94%